A quadrupled semitendinosus only anterior cruciate ligament reconstruction with tibial suspensory fixation - Ballal, Madan Mohan; Chebbi, Pavankumar (International Journal of Medical Research and Review, 2016)
Purpose: Study is designed to analyze the postoperative outcome of arthroscopic ACL reconstruction with quadrupled semitendinosus tendon autograft fixed in femoral tunnel using tight rope and in the tibial tunnel using suture disc. Methods: A prospective study on a continuous series of 102 patients, operated for ACL rupture, using the same technique, from September 2010 to March 2013. Results:The longest follow-up was at 24 months. At 2 year follow-up the mean International Knee Documentation Committee (IKDC 1999) evaluation score revealed that 63.7% had a normal overall grade A. The mean Lysholm score improved from 59.4 to 92.4 at follow-up. The improvement in the limb symmetry index by single hop test was statistically significant. Laxity assessment at 12 months showed 87.2% had a grade 0 or 1 Lachman laxity with a hard end point. Patients had no motion deficit and the knee was stable in deep flexion and retained their strength during internal rotation of the knee. Conclusion: a quadrupled semitendinosus graft was adequate in order to be used alone as a four-strand graft and to get a minimum length and thickness for our graft construct. This enhanced our post-operative rehabilitation by contribution to stability in deep flexion and retaining the strength during internal rotation of the knee. It is cost effective to use atightropeat the femoral end and suture disc at the tibial end as compared to an aperture fixation by a bioscrew.